Enhancing tourism awareness and digital promotion skills of Lok Baintan Floating Market Vendors - Dewi Rachmawati; Ayu Rakhmi Tiara Hamdani; Latifa Ramonita; Jati Paras Ayu; Yesi Pandu Pratama Wibowo (University of Merdeka Malang, 2026)
This community service activity aims to improve the understanding of traders at the Lok Baintan Floating Market regarding tourism potential and digital literacy as a strategy to strengthen the destination's attractiveness and competitiveness. The target partners are floating market traders who interact directly with tourists, but most of them lack an adequate understanding of tourism concepts, service quality, and the use of digital media for promotion. The program was implemented through interactive lectures and participatory discussions. Evaluation was carried out through participant feedback and a comparison of knowledge before and after the activity. Results showed an increase in participants' understanding of the importance of tourism, cleanliness, service quality to tourists, and basic skills in creating simple promotional content through social media, as evidenced by a comparison of pretests and posttests distributed. Participants demonstrated high motivation in this activity and will apply it in their daily lives as traders at the Lok Baintan floating market. Observations after the training also showed improvements in the content produced by several participants. Further mentoring in the form of ongoing digital content training and strengthening promotional networks is needed to optimize the program's impact.